Development of weaving section flow model of conventional roundabout / Jezan Md Diah - Md Diah, Jezan (2012)
Roundabout has been used and becomes popular in sub-urban residential areas as one of a viable traffic control system at intersections. At roundabout vehicles need to make a circulatory movement before exiting to their respective directions without having to stop, thus minimize delay. Studies on roundabout capacity and performance mostly focus on geometric configuration and flow at the entry, on the basis and acceptance of offside priority rule. Studies had shown that offside priority is most appropriate and efficient with small and mini roundabout.